IDENTIFIKASI KOMPOSISI KEPADATAN SAMPAH LAUT (MARINE DEBRIS) DI WILAYAH PESISIR PULAU PELAPIS KEPULAUAN KARIMATA - Ary Chandra; Zan Zibar; Sofi Siti Shofiyah (JKP - Jurnal Kelautan dan Pesisir, 2024)
Pelapis Island is part of the Karimata Islands which are located in North Kayong Regency, West Kalimantan. The island, which is located west of the Karimata Strait and close to the Karimata Islands Marine Nature Reserve, has tourism potential and abundant natural resources that can be utilized by the local community and the government. The cleanliness of the marine environment needs to be ensured in order to support sustainable economic continuity and support the tourism industry sector. This research aims to determine the density of marine debris using the shoreline survey method to determine the beach cleanliness index according to the clean-coast index (CCI), analysis of waste weight and type of waste was carried out at three stations spread across the coast of the island. The type of waste that dominates is wood with waste weight reaching 68% from the three stations. Plastic types with 21%, metal types with 7%, rubber types with 3% and then glass types with 1%. The beach cleanliness index measured at each research station showed different results. Based on the results of the CCI analysis, station 1 received a score of 35 and was included in the very dirty category, Statsuin 2 received a score of 12.96, which was included in the dirty category, a fairly low score at station 3, namely 4.04, which was included in the clean category. Overall, the results of data collection from three research stations show that Pelalui Island still has the potential to become a beach tourism destination by continuing to increase efforts to maintain cleanliness and environmental sustainability.